Compositional dependence of anomalous thermal expansion in perovskite-like ABX3 formates. Issue 10 (19th October 2015) - Collings, Ines E.; Hill, Joshua A.; Cairns, Andrew B.; Cooper, Richard I.; Thompson, Amber L.; Parker, Julia E.; Tang, Chiu C.; Goodwin, Andrew L.
Abstract : Thermal expansion in ABX3 formates is correlated to the size and molecular anisotropy of the A- and B-site cations. Abstract : The compositional dependence of thermal expansion behaviour in 19 different perovskite-like metal–organic frameworks (MOFs) of composition [A I ][M II (HCOO)3 ] (A = alkylammonium cation; M = octahedrally-coordinated divalent metal) is studied using variable-temperature X-ray powder diffraction measurements. While all systems show essentially the same type of thermomechanical response—irrespective of their particular structural details—the magnitude of this response is shown to be a function of A I and M II cation radii, as well as the molecular anisotropy of A I . Flexibility is maximised for large M II and small A I, while the shape of A I has implications for the direction of framework hingeing.